Answer: 144
Explanation:
First, find the x-values where the equations intersect:
2x² = -2x² - 8x + 32
4x² + 8x - 32 = 0
4(x² + 2x - 8) = 0
(x + 4)(x - 2) = 0
x = -4 and x = 2 (see graph to confirm these values)
Now, find the area under the curve:
![\int\limits^(2)_(-4) [(-2x^2-8x+32)-(2x^2)]dx\\\\\\=\int\limits^(2)_(-4) (-4x^2-8x+32)dx\\\\\\=\bigg(-(4)/(3)x^3-(8)/(2)x^2+32x\bigg)\bigg|\limits^2_(-4)\\\\\\=\bigg(-(4)/(3)(2)^3-4(2)^2+32(2)\bigg)-\bigg(-(4)/(3)(-4)^3-4(-4)^2+32(-4)\bigg)\\\\\\=\bigg(-(32)/(3)-16+64\bigg)-\bigg((256)/(3)-64-128\bigg)\\\\\\=\bigg((112)/(3)\bigg)-\bigg(-(320)/(3)\bigg)\\\\\\=(432)/(3)\\\\\\=\large\boxed{144}](https://img.qammunity.org/2020/formulas/mathematics/college/hqd3kipysze8rx0l52qagpx5fn5hjmj283.png)
Answer: 4.5
Explanation:
First, find the x-values where the equations intersect:
x+3 = x² + 1
0 = x² - x - 2
0 = (x - 2)(x + 1)
x = 2 and x = -1 (see graph to confirm these values)
Now find the area under the curve:
![\int\limits^(2)_(-1) [(x+3)-(x^2+1)]dx\\\\\\=\int\limits^(2)_(-1) (-x^2+x+2)dx\\\\\\=\bigg(-(x^3)/(3)+(x^2)/(2)+2x\bigg)\bigg|\limits^2_(-1)\\\\\\=\bigg(-(2^3)/(3)+(2^2)/(2)+2(2)\bigg)-\bigg(-((-1)^3)/(3)+((-1)^2)/(2)+2(-1)\bigg)\\\\\\=\bigg(-(8)/(3)+2+4\bigg)-\bigg((1)/(3)+(1)/(2)-2\bigg)\\\\\\=\bigg((10)/(3)\bigg)-\bigg(-(7)/(6)\bigg)\\\\\\=(9)/(2)\\\\\\=\large\boxed{4.5}](https://img.qammunity.org/2020/formulas/mathematics/college/ahpirx60ezmiqfovd1u4hnakvieg9ar4bv.png)